2016
DOI: 10.9734/ajaees/2016/28892
|View full text |Cite
|
Sign up to set email alerts
|

Training Needs of Agricultural Extension Agents Using Borich Needs Assessment Model

Abstract: The objective of this study is to examine the training needs of agricultural extension workers in various provinces of Iraq. Validate them and develop a method of identification of training needs for agricultural extension agents. The data collected were analyzed by determination of the mean of the responses from the respondents and one-way of Variance (ANOVA). Using Borich need Assessment model for training needs, the questionnaire survey was adopted for a population of 300 professionals in clients, consultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…So far, in many studies around the world, the training needs have been investigated in various fields. For example, Man et al [24] examined the learning needs of agricultural extension staff in Iraq and indicated that there was a significant relation among marital status, place of employment, training, and number of training courses, and extension agents decided that they needed training in agricultural research areas. A study in Northeast India by Singh et al [25] showed that the first and foremost activity in planning a good training program is the assessment of training needs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…So far, in many studies around the world, the training needs have been investigated in various fields. For example, Man et al [24] examined the learning needs of agricultural extension staff in Iraq and indicated that there was a significant relation among marital status, place of employment, training, and number of training courses, and extension agents decided that they needed training in agricultural research areas. A study in Northeast India by Singh et al [25] showed that the first and foremost activity in planning a good training program is the assessment of training needs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Search data gathered through the questionnaire, the interview with 120 properly addressed, after compiling the data are encoded and discharged and scheduling to fit the statistical analysis methods used, and used some appropriate statistical methods as a percentage, and average The arithmetic mean, standard deviation, as well as using iterative Tables to display data, use the software SPSS (Statistical Program of Social Sciences version 22) [10].…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…This generally depends on the family's economic and pension income level, where the more well it is, the more appropriate it will be. An indication that the number of sources was not high, so these villages need to diversify and diversify their sources of information by providing training courses and guidance publications to keep pace with developments in the agricultural field and raise the standard of living [1,10].…”
Section: Characteristics Of Rural Womenmentioning
confidence: 99%
“…Extension as a non-formal means of education provides advisory services by the use of an educational process to assist farmers to acquire knowledge and skills to effectively catch up with their own needs and problems they face in their very socio-economic contexts (Khan, 2016). Nowadays, a key universal challenge that requires farmers" competence is how to make food security possible for the world growing population and to ensure long-lasting sustainable development (Man et al, 2016). The agricultural extension agents must seek solutions to the constraints that limit the efficiency and productivity of other actors in the chain, and the development of cooperative relationships among actors (Ammani and Abdullahi, 2015).…”
Section: Introductionmentioning
confidence: 99%